Postharvest Losses, Current Issues and Demand for Postharvest Technologies for Loss Management in the Main Banana Supply Chains in Sri Lanka - Wasala, W M C B; Dissanayake, C A K; Dharmasena, D A N; Gunawardane, C R; Dissanayake, T M R (Journal of Postharvest Technology, 2014)
Banana is the main fruit crop cultivated in Sri Lanka. It’s a  commercial crop giving high income to the cultivators. It is  distributed from farm gate to consumers through the supply chain  which involves farmer, collector, whole seller, retailer and  transporter and with a high post harvest loss. Therefore, this study  was conducted to assess the present status of the banana supply  chain. A total sample of 100 including farmers, collectors, whole  sellers, transporters and retailers were randomly selected from two  growing areas and a high banana retailing municipal council areas.  Data were gathered through a survey using a questionnaire, key  informant interviews, direct observations and secondary sources.  The study revealed that the banana supply chain follows the  conventional chain with some deviations. All whole sellers were  acting as bulk transporters. Majority of stakeholders preferred and  transported bananas as whole bunches bulk packed in vehicles.  Preference in selling in retail outlets were also as intact bunches.  The commonly used transportation vehicles were two wheel  tractors, open trucks, and lorries. The total postharvest loss of  banana was 20 % from farm gate to retailer. A suitable bulk  packing method should be introduced to reduce the post harvest  loss of banana.
Keywords: Banana; Packaging methods Post harvest loss Supply; chain